Edukasi Pola Asuh Positif Dan Pergaulan Dalam Moderasi Beragama Sebagai Program Pengentasan Stunting Di Desa Pehwetan - Anam, Masrul; Aprilia Anggraini Ali (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2023)
Stunting is a health problem that is currently being discussed in Indonesia. This is no exception in Pehwetan Village, Papar Sub-district, Kediri District. The case of stunting in Pehwetan Village is quite high, which is ranked first in Papar Sub-district, Kediri District. One way to reduce the stunting rate in Pehwetan Village is by improving the right parenting style. Indirectly, the choice of parenting patterns can affect stunting cases, parents who do not understand parenting patterns in meeting the nutritional needs of children, both child nutrition while in the womb and nutrition after the child is born, such as related to food security and environmental sanitation. In addition to the high number of stunting cases, another interesting thing is the community life that can coexist amid religious diversity. The research method used is the PAR research method in which a scientific problem study is carried out in order to direct, improve, and evaluate decisions and actions of the research object.. The results of this study are that there is an increase in understanding obtained by socialization participants with evidence of an increase in scores on the post test. Judging from the level of knowledge of the participants, it shows that they also have the motivation and encouragement to improve themselves in learning and add to their insights about the importance of parenting and getting to know association in religious moderation